Authenticity in health education for adolescents: a qualitative study of four health courses. Issue 2 (28th January 2014) - Grabowski, Dan; K. Rasmussen, Katrine
Abstract : Purpose: – The purpose of this paper is to explore different kinds of authenticity in four health courses for adolescents. In school-based approaches to health education it is often difficult to present health in ways that make sense and appeal to adolescents. Authenticity, as a health-pedagogical concept which focuses on the quality or condition of being believable, trustworthy or genuine, has the potential of providing an analytical framework as well as practical recommendations for this challenge. Design/methodology/approach: – This was a qualitative study based on 23 group interviews with a total of 114 adolescents and 12 individual interviews with their teachers. The data were iteratively analyzed and categorized using guidelines for content analysis. The study used a theoretical construct focusing on participation, knowledge and health identity, as each of these three elements affects aspects of authenticity when applied to a health education context. Findings: – The analysis revealed four interdependent categories of authenticity: first, authentic connections/relations; second, authentic instructors; third, authentic themes; and fourth, authentic methods/activities. In each of the four categories the paper presents analytical tools for researchers and practical recommendations for health education professionals. Originality/value: – The paper presents a new and innovative model with four categories of authenticity that provide health practitioners with important knowledge about why and how health education might wish to focus on authenticity in order to provide conditions that create a significant health educating effect for all adolescents, not just for the ones who are already healthy.